Effect of tocotrienol on the activities of cytosolic glutathione-dependent enzymes in rats treated with 2-acetylaminofluorene - Shamaan, Nor Aripin; Wan Ngah, Wan Zurinah; Ibrahim, Rusli; Jarien, Zanariah (1993)
The effect of tocotrienol on the activities of glutathione S-transferases (GSTs), glutathione reductase (GR) and glutathione peroxidase (GPx) in rats given 2-acetylaminofluorene (AAF) was investigated over a 20 week period. Liver and kidney GST and liver GR activities were significantly increased after AAF administration. Kidney GPx activities were significantly affected; activity assayed with cumene hydroperoxide (cu-OOH) was increased but activity assayed with H2O2 was reduced. Supplementation of the diet with tocotrienol in the AAF-treated rats reduced the increase in enzyme activities. Tocotrienol on its own had no effect on the enzyme activities. © 1993.